Modeling the Wintering Habitat Distribution of Oriental Honey Buzzards in West Java Indonesia with Satellite Tracking Data Using Logistic Regression - Syartinilia Syartinilia; Yeni Aryati Mulyani; Afra Donatha Nimia Makalew; Hiroyoshi Higuchi (Bogor Agricultural University, Indonesia, 2022)
Oriental honey buzzards (OHBs, Pernis ptilorhynchus) are one of migratory raptor from Japan to Indonesia which is widely recognized as indicator species reflecting the conditions of their habitat. Since 2003, OHBs have been satellite-tracked in their wintering grounds in Indonesia. Less information available on wintering areas in the west Java, which hampers the OHB conservation efforts. This paper proposes a new approach for predicting the probability models of the wintering habitat distribution of OHBs with the presence data derived from satellite tracking using logistic regression analysis coupled with RAMAS GIS. This spatial model was locally constructed from the data concerning Talaga Bodas and its surrounding areas and extrapolated for the entire West Java region. The best predicted probability model successfully characterized the distribution of the OHB wintering habitat using slope (25–40%), elevation (0–300 m and >1,000 m), and land cover (forest, paddy field, and water body). The extrapolation model generated potential areas of the wintering habitat distribution covering an area of 3013.13 km2 (8.11% of West Java). These areas were predominantly located outside the protected areas (94.04%). The modeling approach proposed herein may be used to study other migratory species that are tracked using satellite or other navigation technologies.